(untitled) - Stalder, Marcel

Petrology and mineral chemistry of sulphide ores and associated metalliferous rocks of the Gamsberg Zn-Pb deposit, South Africa : implications for ore genesis and mineral exploration (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD)--University of Stellenbosch, 2004.